Synthesis and biological evaluation of some new 1,3,4-thiadiazole and 1,2,4-triazole derivatives from L-methionine as antituberculosis and antiviral agents [L-Metiyoninden hareketle elde edilen bazı yeni 1,3,4-tiyadiazol ve 1,2,4-triazol türevlerinin sentezi, antitüberküler ve antiviral etkilerinin değerlendirilmesi] - (:unkn) unknown (Marmara University, 2015)
Some novel 1,3,4-thiadiazole [5-8] and 1,2,4-triazole [9-12] derivatives carrying amino acid moiety were synthesized starting from L-methionine. 1,3,4-Thiadiazole and 1,2,4-triazole scaffolds were prepared by cyclocondensation of the corresponding thiosemicarbazide and finally converted to their thiourea derivatives. Structures of the synthesized compounds [4-12] were confirmed by IR, 1H-NMR and 13C-NMR spectral data and elemental analysis. Synthesized compounds were evaluated for their antiviral and antibacterial activity. Of the screened compounds, N-{3-(methylsulfanyl)- 1-[5-(phenylamino)-1,3,4-thiadiazole-2-yl]propyl}benzamide [5] was identified as the most potent inhibitor of Influenza A H3N2 virus with an EC50 value of 31.4 μM, which serves as a lead compound for prospective development. The antituberculosis activity screen of the synthesized compounds revealed 1-[4-(4-chloro-(3-trifluoromethyl)phenyl]-3-[3-(methylsulfanyl)- 1-(4-phenyl-5-thioxo-4,5-dihydro-1H-1,2,4-triazole- 3-yl)propyl]thiourea [12] as the most active compound against M. tuberculosis H37Rv strain (MIC : 30.88 μM) but the compound proved not selective. © 2015, Marmara University. All rights reserved.
Keywords: 1,2,4-triazoles; 1,3,4-thiadiazoles; Antituberculosis activity; Antiviral activity; Influenza; Thioureas